Rumination as a Mediator between Childhood Trauma and Adulthood Depression/Anxiety in Non-clinical Participants - Kim, Ji S.; Jin, Min J.; Jung, Wookyoung; Hahn, Sang W.; Lee, Seung-Hwan (Frontiers in Psychology, 2017)
Objective: Although there is strong evidence that childhood trauma is associated with the development of depression and anxiety, relatively few studies have explored potential mediating factors for this relationship. The present study aimed to evaluate the mediating role of rumination in the link between childhood trauma and mood status such as depression, anxiety and affective lability. Material and Methods: Two hundred and seven non-clinical participants completed the Childhood Trauma Questionnaire, the Ruminative Response Scale, the Beck Depression Inventory, the State Anxiety Inventory, and the Affective Lability Scale. Structural equation modeling was used to evaluate the results. Results: Our results supported that rumination is a meaningful mediator between childhood trauma and depression/anxiety in non-clinical participants. The mediation model indicated that childhood trauma and its subtypes are linked to depression and anxiety through three subtypes of rumination, thereby supporting a significant indirect relationship (Standardized coefficient [SC] = .56, p < .001 for the path from trauma to rumination; SC = .67, p < .001, from rumination to mood). The direct relationship between childhood trauma and mood symptoms was also significant in a model including rumination (SC = .68, p < .001). The mediation effect of rumination in the relationship between childhood trauma and mood was more predominant in female participants. Conclusions: The present study found that rumination mediates the influence of childhood trauma on the development of mood symptoms in non-clinical participants. Childhood trauma appears to be a critical determinant for developing symptoms of depression and anxiety.